COMPARATIVE ANALYSIS OF ISLAMIC CULTURE IN INDONESIA AND THAILAND: INFLUENCES, PRACTICES, AND SOCIETAL IMPACTS - Alhempi, R. Rudi; Suasungnern, Sineerat (Penerbit Lafadz Jaya, 2024)
This study examines the similarities and differences in Islamic culture between Indonesia and Thailand, two Southeast Asian nations with significant Muslim populations. Although both countries are diverse in their cultures, the expressions of Islam are shaped by historical, social, and political contexts. Through a qualitative comparative analysis, the research highlights key cultural practices, religious interpretations, and community engagement in both nations. Indonesia, known for its moderate Islamic practices, shows a blend of local traditions, while Thailand presents a unique perspective with its predominantly Buddhist landscape influencing its Islamic minority. The findings suggest that the interaction between Islam and local cultures creates distinct manifestations of faith and practice. This paper contributes to understanding the broader implications of religious diversity and cultural identity within Southeast Asia.